Collaborative Governance in Driving MSME Technology Adoption for Smart Economy Acceleration in Yogyakarta - Darumurti, Awang; Fridayani, Helen Dian; Atmojo, Muhammad Eko; Chiang, Li Chun (Journal of Government and Civil Society, 2025)
This research examines the role of Collaborative Governance in encouraging technology adoption by MSMEs to accelerate the smart economy in Yogyakarta. MSMEs have a strategic role in the regional economy, but still face obstacles in digitalization. The Collaborative Governance approach was chosen because it allows active involvement of various stakeholders in supporting the digital transformation of MSMEs. The method used is qualitative with a case study approach. Data were obtained through interviews with the DIY Cooperative and SME Agency and Bapperida, as well as analysis of relevant documents. Data analysis was conducted using interactive model techniques and Nvivo 12 Plus software. The results show that collaboration between the government, private sector, and the MSME community plays an important role in providing digital infrastructure, training, and support for programs such as SiBakul. This process takes place through three main stages: (1) identification of barriers and opportunities, (2) formulation of digitalization strategies, and (3) implementation of technology-based programs. In technology adoption, the highest indicators are perceived benefits and ease of use, indicating MSMEs' awareness of the benefits of technology. Although MSME awareness is high, technology implementation is still constrained in intention and actual use.